Two-point nasomaxillary fixation of the Le Fort I osteotomy: assessment of stability at one year postoperative. Issue 4 (April 2020) - Susarla, S.M.; Ettinger, R.; Preston, K.; Kapadia, H.; Egbert, M.A.
Abstract: The purpose was to assess maxillary position among patients undergoing Le Fort I maxillary advancement with internal fixation placed only at the nasomaxillary buttresses. This was a retrospective study of patients undergoing a Le Fort I osteotomy for maxillary advancement, with internal fixation placed only at the nasomaxillary buttresses. Demographic and cephalometric measures were recorded. The outcome of interest was the change in maxillary position between immediately postoperative (T1), 6 weeks postoperative (T2), and 1 year postoperative (T3). Fifty-eight patients were included as study subjects (32 male, 26 female; mean age 18.4 ± 1.8 years). Twenty-five subjects (43.1%) had a diagnosis of cleft lip and palate. Forty-three subjects (74.1%) had bimaxillary surgery, 16 (27.6%) had bone grafts, and 18 (31.0%) had segmental maxillary osteotomies. At T3, there were no subjects with non-union, malunion, malocclusion, or relapse requiring repeat surgery. Mean linear changes between T1 and T3 were ≤1 mm. Mean angular changes between T1 and T3 were <1°. There was no significant difference in stability in multi-segment maxillary osteotomies ( P = 0.22) or with bone grafting ( P = 0.31). In conclusion, anterior fixation alone in the Le Fort I osteotomy results in a stable maxillary position at 1 year postoperative.